2019
DOI: 10.1103/physrevapplied.12.044062
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Mo 66 Re 34 SQUID-on-Tip for High-Field Magnetic and Thermal Nanoimaging

Abstract: Scanning nanoscale superconducting quantum interference devices (SQUIDs) are gaining interest as highly sensitive microscopic magnetic and thermal characterization tools of quantum and topological states of matter and devices. Here we introduce a novel technique of collimated differential-pressure magnetron sputtering for versatile self-aligned fabrication of SQUID-on-tip (SOT) nanodevices, which cannot be produced by conventional sputtering methods due to their diffusive, rather than the required directional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Hz. The flux sensitivity is comparable to that of micrometer-scale planar scanning SQUIDs shown by Huber et al [24] and better than that of previously reported submicrometer SQUID-on-tip probes made from Al [18], Nb [19], and Mo 66 Re 34 [26]. The device does not, however, attain the flux sensitivity of Pb SQUID-on-tips [20].…”
supporting
confidence: 53%
“…Hz. The flux sensitivity is comparable to that of micrometer-scale planar scanning SQUIDs shown by Huber et al [24] and better than that of previously reported submicrometer SQUID-on-tip probes made from Al [18], Nb [19], and Mo 66 Re 34 [26]. The device does not, however, attain the flux sensitivity of Pb SQUID-on-tips [20].…”
supporting
confidence: 53%
“…The SOTs were fabricated using three-step deposition of superconducting film on a pulled quartz pipette as described previously [54,55]. A Pb SOT of 48 nm diameter, fabricated using thermal deposition [56], displayed thermal sensitivity of 1.9 µK/Hz 1/2 and operated in field of up to 1 T, while MoRe SOT of 100 nm diameter, fabricated using a recently introduced method of collimated sputtering [57], had thermal sensitivity of 1.1 µK/Hz 1/2 at 0 T and operated in field of up to 5 T with sensitivity of 3.3 µK/Hz 1/2 . The thermal imaging (as well as the rest of the measurements) was carried out at 4.2 K in presence of about 60 mbar pressure of He exchange gas as described previously [32,38,43].…”
Section: Squid-on-tip Thermal Imaging and Scanning Gate Microscopymentioning
confidence: 99%
“…Nanoscale superconducting quantum interference devices (nano-SQUIDs) are considered a promising tool for achieving the goal of single-electron spin detection on account of their performance as a flux-to-voltage transformer and low sensitivity to external flux noise . Over the last 2 decades, a wide range of nano-SQUIDs have been demonstrated using a variety of materials, device geometries, and fabrication techniques and applied to magnetometry of magnetic nanoparticles. Many of these have exploited weak links formed using Dayem bridges, which are desirable due to their low capacitance, high current density, and insensitivity to in-plane magnetic fields, suitable for high-magnetic-field applications. However, the operational magnetic fields reported so far for nano-SQUIDs are below 1 T, and focus has been on cases where the high magnetic field is applied only parallel to the plane of the SQUID loop. , Superconducting diamond, achieved through boron doping with a density exceeding 4.5 × 10 20 cm –3 , is considered an excellent candidate for D.C. SQUID technology because of its high critical field and critical current density. A micrometer-sized D.C. SQUID has been demonstrated using thin-film, boron-doped nanocrystalline diamond (NCD) with a Dayem bridge architecture and a loop size of 2.5 μm, reporting operation in a perpendicular applied magnetic field of up to 4 T, and a flux noise sensitivity of in an applied field of 0.3 mT.…”
Section: Introductionmentioning
confidence: 99%